O Estudo de História da África e da cultura afro-brasileira: uma investigação na Escola Municipal Machado de Assis - Ituiutaba-MG (2017) - Santos, Camilla (2019)
This work was developed in the Program of Post-graduation in Education by the Federal University of Uberlândia (PPGED / UFU). The research is based on the following questions: How have the contents related to the History of Africa and Afro-Brazilian culture been worked in school? How do the History teachers approach such content in the daily life of classes? How does the teaching of these contents mark the training of students? This way, the general objective was to identify and reflect on the forms that contents related to the History of Africa and Afro-Brazilian culture have been worked in the Municipal School Machado de Assis, located in Ituiutaba-MG, Brazil. Specifically, we sought to: i) present and analyze the plot scenario: the city of Ituiutaba-MG, Brazil, evidencing E. M. Machado de Assis; ii: analyze, through the voices of the History teachers the formation, knowledge and practices in teaching contents related to the History of Africa and Afro-Brazilian culture; iii: reflect on what the students of the 9th grade of elementary school in the school investigated say about issues related to the History of Africa and Afro-Brazilian culture. As referential theorists the ones who approach the decolonial studies, teaching of History and youth. This is a qualitative research that used different instruments: the observation of history classes and the making of field notes, the technique of the focus group and an interview with the History teachers. It is believed that this research can contribute to the formation of History teachers and their practices in the classroom, especially what has been produced in the epistemological field of Law 10.639/03.